(untitled) (International Journal of Engineering and Computer Science, 2016)
Nowadays for the analysis of ECG signals and its interpretation, Signal processing plays an important role. ECG signal processing has an important objective to give society a filtered result with maximum accuracy and the information which is not readily extracted from visual assessment of ECG signal. ECG signals are obtained by placing electrodes on the body surface of a human being. It leads to contamination of noise to ECG signals. These noises are baseline wander, power-line interference, electromyographic (EMG) noise, electrode motion artifacts and much more. These noises act as hurdles during processing of ECG signal and thus for removal and rejection of such noise, pre-processing of ECG signal is an important task. Therefore on a primary basis, filtering techniques are used for preprocessing of any signals and similarly for ECG signals. The only care for ECG signal should be taken that the real information should not be distorted. In this paper, the main concentration will be on filtering of the baseline wander and the power-line interference.